Agricultural input subsidies : the recent Malawi experience - Chirwa, Ephraim W.; Dorward, A. (Andrew) (Oxford : Oxford University Press, 2014)
This title provides a detailed, comprehensive, and objective analysis of Malawi's agricultural input subsidy programme, its history, implementation, achievements, and shortcomings.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 5, 2013).
Keywords: Agricultural subsidies -- Malawi; Economic development -- Malawi; Agricultural subsidies -- Developing countries; Economic development -- Developing countries